Kedudukan Anak Angkat Terhadap Harta Warisan Orang Tua Angkat - Windani, Sri; Meiliawati, Indri (Sekolah Tinggi Ilmu Hukum Graha Kirana, 2023)
AbstractThe purpose of marriage is to form a family that is sakinah mawaddah wa rahmah (a family of peace, love, and affection) which ideally consists of a father, mother, and children. A marriage without children feels incomplete. Children increase family happiness. As a result, many couples adopt children with the aim of having children and providing love and a decent life to their adopted children. Adopted children are usually cared for and loved from birth. The problem is that adopted children who are immature and unable to live on their own are neglected when their parents die. After the adoptive parents die, their closest relatives take over the inheritance because they feel more entitled to the property they have given them. This research method uses a normative legal approach, because this research refers to legal standards regulated in legislation and in the community relating to inheritance, child adoption, and mandatory wills. Child adoption is permitted by Islamic law, as long as it does not affect blood relations, guardianship, and inheritance with adoptive parents. The child retains the name of his biological father and becomes the heir of his biological parents. If the adoptive parents are still alive and do not give a will for their property to their adopted children, Islamic law provides a solution by giving them